Compliance with clinical guidelines for whiplash improved with a targeted implementation strategy: a prospective cohort study - Rebbeck, Trudy (BioMed Central, 2013)
BACKGROUND: Implementation strategies for clinical guidelines have shown modest effects in changing health professional’s knowledge and practice, however, targeted implementations are suggested to achieve greater improvements. This study aimed to examine the effect of a targeted implementation strategy of the Australian whiplash guidelines on health professionals’ knowledge, beliefs and practice and to identify predictors of improved knowledge. METHODS: 94 health professionals (Physiotherapists, Chiropractors and Osteopaths) who manage whiplash participated in this study. Prior to their inclusion in the study, health professionals were classified as compliant with clinical guidelines for whiplash (n = 52) or non-compliant (n = 42), according to a record of clinical practice. All participants completed a 2- day interactive workshop with outcomes measured at baseline and 3 months following the workshop. The workshop was delivered by opinion leaders, with the educational content focused on the pre-identified knowledge and practice gaps in relation to clinical guidelines for whiplash. Knowledge and health professional beliefs were assessed by a questionnaire and professional practice by record of clinical practice. RESULTS: Participants significantly increased knowledge (p < 0.0001) and were more likely to be compliant with the guidelines at follow-up (compliant at baseline 58%, follow-up 79%, p = 0.002). Health professional belief systems significantly changed to be more behavioural (p = 0.02) and less biomedical (p = 0.000). Predictors of improved knowledge were baseline knowledge (parameter estimate = -0.6, p = 0.000) and profession (parameter estimate = -3.8, p = 0.003) (adj R(2) = 35%). CONCLUSIONS: A targeted implementation strategy improved health professional’s knowledge and clinical practice so that they became more compliant with clinical guidelines for whiplash. In addition health professionals’ belief systems significantly changed to be more behavioural in orientation. Baseline knowledge and profession predicted 35% of the variance in improved knowledge.